Geosynthetic-reinforced and jet grout column-supported embankments on soft soils: numerical analysis and parametric study - José Leitão Borges (2011)
Using a computer code based on the finite element method, a study is conducted to analyse the timedependent behaviour of a geosynthetic-reinforced and jet grout column-supported embankment on soft soils, as well as the influence of three factors: the embankment height, the elastic modulus of column and the column spacing. The cylindrical unit cell formulation is used. The numerical model incorporates the Biot consolidation theory with soil constitutive relations simulated by the pqh critical state model. Special emphasis is given to the analysis of several parameters: settlement, excess pore pressure, effective stress, stress level, tension in the geosynthetic, soil arching effect and overall efficiency coefficient. 2011 Elsevier Ltd. All rights reserved.